The Bone Marrow Microenvironment Mechanisms in Acute Myeloid Leukemia - Pimenta, Débora Bifano; Varela, Vanessa Araujo; Datoguia, Tarcila Santos; Caraciolo, Victória Bulcão; Lopes, Gabriel Herculano; Pereira, Welbert Oliveira (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow (BM) is a highly complex tissue that provides important regulatory signals to orchestrate hematopoiesis. Resident and transient cells occupy and interact with some well characterized niches to produce molecular and cellular mechanisms that interfere with differentiation, migration, survival and proliferation in this microenvironment. The acute myeloid leukemia (AML), the most common and severe hematological neoplasm in adults, arises and develop in the BM. The osteoblastic, vascular, and reticular niches provide surface co-receptors, soluble factors, cytokines, and chemokines that mediate important functions on hematopoietic cells and leukemic blasts. There are some evidences of how AML modify the architecture and function of these three BM niches, but it has been still unclear how essential those modifications are to maintain AML development. Basic studies and clinical trials have been suggesting that disturbing specific cells and molecules into the BM niches might be able to impair leukemia competencies. Either through niche-specific molecule inhibition alone or in combination with more traditional drugs, the bone marrow microenvironment is currently considered the potential target for new strategies to treat AML patients. This review describes the cellular and molecular constitution of the BM niches under healthy and AML conditions, presenting this anatomical compartment by a new perspective: as a prospective target for current and next generation therapies.